Hypermethylation of brain natriuretic peptide gene is associated with the risk of rheumatic heart disease. Issue 1 (16th January 2017) - Li, Ni; Zheng, Dawei; Sun, Lebo; Shi, Huoshun; Zhu, Xiuying; Xu, Guodong; Wang, Qinning; Zhu, Caimin; Shao, Guofeng
Abstract : To investigate the contribution of brain natriuretic peptide (BNP) promoter DNA methylation to the risk of rheumatic heart disease (RHD) and the influence of warfarin anticoagulant therapy on BNP methylation levels for RHD patients after surgery. BNP methylation levels were determined by bisulfite pyrosequencing from plasma samples of RHD patients compared with healthy controls. Several factors influencing the RHD patients were included like age, smoking and cholesterol levels. A fragment of five CG sites (CpG1–5) in the promoter region of BNP gene was measured. BNP gene hypermethylation was found in CpG4 and CpG5 in RHD patients compared with non-RHD controls. A significant difference was also observed between RHD patients with long-term administration of warfarin and RHD patients who had recently undergone an operation. Moreover, single CpG4 and CpG5 analysis revealed a significant increase in methylation levels in men. BNP gene body hypermethylation is associated with the risk of RHD, and also influenced by the warfarin anticoagulant therapy of RHD patients after surgery, which could represent novel and promising targets for therapeutic development.